Orígenes y problemas de la escuela rural en el Ecuador: 1870-1930 (Estudios) - Luna Tamayo, Milton (2022)
The research concludes that the federal state’s limited concern over fostering rural schooling, in particular educating indigenous peoples, stemmed not only from the shortage of resources or the inefficiency of government administration services, but also from more deeply rooted factors, namely, the decision of the country’s ruling elites to focus the state’s policy priorities on bolstering state building and modernization, thus excluding the indigenous and rural sectors and giving further impetus to cities and the middle class, two trends that emerged not only in Ecuador but also in Latin America as a whole.